(untitled) (Journal of Hama University, 2025)
The Syrian women’s novel, at this delicate stage in Syria’s contemporary history, is considered a turning point in the history of Syrian literature, because of the social, political and cognitive connotations it carries on many levels. The social political upheavals that surrounded Syrian society cast their cognitive and aesthetic shadows on the novel at that time, not to mention that Syria’s exit from the French occupation had a profound impact in creating a particularly important social novel system. Syrian society has preserved many of the social ills and outdated traditions that the novel took a stand against. Alienation, social oppression, and injustice were among the issues that women fought, and for that they paid a heavy price on the path to social-cognitive freedom. The women’s novel - with its chronological escalation - seemed to be the focus of violent tensions and unusual conflicts between women and their painful reality, which women novelists viewed in multiple forms and perspectives.